Building Integrated Solar Thermal Systems - Kalogirou, Soteris A. (My University, 2015)
With buildings accounting for 40% of primary energy requirements in EU and the implementation of the Energy Performance of Buildings Directive, developing effective energy alternatives for buildings is imperative. The increasing role for renewables implies that solar thermal systems (STS) will have a main role as they contribute directly to the heating and cooling of buildings and domestic hot water. Meeting building thermal loads will be primarily achieved through an extensive use of renewables, following standard building energy saving measures. These systems are typically mounted on building roofs with no attempt to incorporate them into the building envelope creating aesthetic challenges, space availability issues and envelope integrity problems. This paper aims to give a survey of possible solutions of STS integration on the building roofs and façades, applied so far. Through the presentation of the various examples, the advantages of integration are revealed.
Keywords: Solar energy; Solar collectors; Buildings; Integration into facades